Experimental modeling to optimize the sonication energy in water. (15th October 2020) - Zaib, Qammer; Ahmad, Farrukh
Graphical abstract: Highlights: Sonication energy generated in aqueous systems calibrated using calorimetric method. Sonication energy modeled against sonicator's controllable variables. Sensitivity of input variables on sonication energy determined. Sonication energy depended chiefly on sonicator's vibration amplitude. Sonication energy optimized by manipulating combination of sonicator's variables. Abstract: This study describes the calibration, modeling, and optimization of (ultra)sonication energy generated by a probe sonicator. Calibration was achieved via simple calorimetry and the effects of four primary variables (i.e. sonication time, vibration amplitude, and pulse-on/-off duration) on sonication energy were utilized to generate an optimal mathematical model via response surface methodology (RSM). Ultrasonication was performed for a time period of 20–1180 sec/centiliter, with the vibration amplitude ranging from 36 to 180 µm, and the pulse-on/-off duration limited to ≤60 sec. We observed approximately 66% of electrical energy conversion to sonication energy in water. The sensitivity of each variable was quantified and optimized with respect to the goal of conserving overall electrical energy. It was found that the quantity of sonication energy, delivered to an aqueous system, depended chiefly on the vibration amplitude. In our experimental setup, the process of sonication was optimal for a sonication period of 890 sec/centiliter while sustaining a vibration amplitude of 144 μm and a pulse-on/-off cycle of 39/30 sec. The procedure demonstrated here can be utilized for uniformly optimizing the sonication energy required for extraction, disintegration, lysis, emulsification, milling, homogenization, de-agglomeration, and dispersion for probe sonication systems applied to aqueous systems.